Response of Planktonic and Benthic Microbial Community to Urban Pollution from Sewage Discharge in Jilin Reach of the Second Songhua River, China. Issue 10 (10th March 2014) - Lin, Shanshan; Wang, Ying; Lin, Jifang; Quan, Chengshi
<x xml:space="preserve">Abstract</x> To investigate the role of the planktonic/benthic bacterial community in sewage polluted water, the biomass, suspended solids (SS), and chemical oxygen demand (COD) were measured downstream from a discharge point (P0) and reference water point (U1) in the Second Songhua River, China. In addition, 16S rDNA community was analyzed using MOTHUR and the bacterial abundance was assayed by real‐time quantitative PCR. The results showed that the SS (14 mg L−1) and COD (11.80 mg L−1) in the reference water were much lower than in the polluted water (SS, 54 mg L−1; COD, 81.79 mg L−1). The bacterial diversity of polluted water had a lower richness than that of sediment at P0. Approximately 80% of the detected planktonic and benthic bacteria were anaerobic/facultative anaerobic bacteria at P0. The most abundance of planktonic bacteria (108 copies ng−1) was observed at 100 m downstream of P0 where more ecological nutrients (COD, 64.07 mg L−1) accumulated. However, the benthic bacterial abundance reached the highest value 50 m downstream of P0 where the COD were not the highest. The relationship between the density of planktonic/benthic microbes and COD suggested that planktonic/benthic microbes possessed high degradation capabilities in river and provided good potential purification for the organic materials discharged from urban sewage.